Exploring Issues in a Networked Public Sphere: Combining Hyperlink Network Analysis and Topic Modeling. (February 2018) - Maier, Daniel; Waldherr, Annie; Miltner, Peter; Jähnichen, Patrick; Pfetsch, Barbara
We propose a methodological approach to analyze the content of hyperlink networks which represent networked public spheres on the Internet. Using the case of the food safety movement in the United States, we demonstrate how to generate a hyperlink network with the web crawling tool Issue Crawler and merge it with the results of a probabilistic topic model of the network's content. Combining hyperlink networks and content analysis allows us to interpret such a network in its entirety and with regard to the mobilizing potentials of specific sub-issues of the movement. We focus on two specific sub-issues in the food safety network, genetically modified food and food control, in order to trace the involved websites and their interlinking structures, respectively.